Free Fibula Flap for the Treatment of Agnathia in a 10-Year-Old With Severe Agnathia-Otocephaly Complex. Issue 1 (11th January 2023) - Cohen, Oriana; Morrison, Kerry A.; Jacobson, Adam; Levine, Jamie; Staffenberg, David A.
Abstract : Agnathia-otocephaly complex (AOC), a first branchial arch defect, is characterized by mandibular hypoplasia or aplasia, ear abnormalities, microstomia, and macroglossia and is a rare and often fatal diagnosis. Herein, the technical considerations and details of mandibular reconstruction using virtual surgical planning (VSP) and a vascularized free fibula flap for further mandibular reconstruction in a 10-year-old boy are presented. The patient's preoperative examination was consistent with agnathia (absence of mandibular symphysis, bilateral mandibular bodies, condyles, coronoids, rami, and temporomandibular joint), severe microstomia, and a Tessier # 30 cleft (maintained to allow oral access until later in treatment). Virtual surgical planning was utilized to plan a 3-segment fibula for the reconstruction of the mandibular symphysis and bilateral body segments, and bilateral costochondral grafts were planned for the rami. To the authors' knowledge, this represents the first application of virtual surgical planning for mandibular reconstruction with a vascularized free fibula flap in a pediatric patient with severe agnathia-otocephaly complex.